Improvement of a Mechanism of Providing Economic Security Of Enterprises in the System of Global Competitiveness - Avanesova, Nina; Volovelska, Irina; Maslova, Valentina; Sukhorukova, Tetiana; KUtkina, Yuliya (International Journal of Engineering and Technology, 2018)
In the context of the interaction of international competitiveness of economic entities and their economic security, it should be noted that globalization of the world economy has one of its consequences a relative equation of the conditions of competition in national markets. As a result of providing by governments the most favored and national regimes, as it was required by international norms of legal regulation of the economy, national and foreign producers find themselves in roughly similar conditions on individual countries or their unions markets. In this case, foreign economic and international security should become a barrier to global threats for the development of national economy and its producers in the global system of world economy. At the same time, the universal requirement imposed on any national economic entity is its competitiveness.